Author Correction: Cohort-wide deep whole genome sequencing and the allelic architecture of complex traits - Arthur Gilly (Nature Portfolio, 2018)
The original version of this Article contained an error in Fig. 2. In panel a, the two legend items “rare” and “common” were inadvertently swapped. This has been corrected in both the PDF and HTML versions of the Article.